Purification and characterization of lectin from fruiting body of Ganoderma lucidum: lectin from Ganoderma lucidum - Thakur, Atul; Rana, Monika; Lakhanpal, T N; Ahmad, Absar; Khan, M I (Biochimica et biophysica acta, 2007)
A novel 114 kDa hexameric lectin was purified from the fruiting bodies of the mushroom Ganoderma lucidum. Biochemical characterization revealed it to be a glycoprotein having 9.3% neutral sugar and it showed hemagglutinating activity on pronase treated human erythrocytes. The lectin was stable in the pH range of 5-9 and temperature up to 50 degrees C. The hemagglutinating activity was inhibited by glycoproteins that possessed N-as well as O-linked glycans. Chemical modification of the G. lucidum lectin revealed contribution of tryptophan and lysine to binding activity. The thermodynamics of binding of bi- and triantennary N-glycans to G. lucidum lectin was studied by spectrofluorimetry. The lectin showed very high affinity for asialo N-linked triantennary glycan and a preference for asialo glycans over sialylated glycans. The binding was accompanied with a large negative change in enthalpy as well as entropy, indicating primarily involvement of polar hydrogen, van der Waals and hydrophobic interactions in the binding.